Measuring the Performance of the Indian Premier League Teams through an Integrated Optimality Analytics by Data Envelopment Analysis Approach - Ashok R., Raju Nellutla, Rajagopalan V. (Mathematical Statistician and Engineering Applications, 2023)
In this present research paper, we evaluate the Indian Premier League Teams Optimality Analytics by CCR, BCC models through Data Envelopment Analysis (DEA) approach and see the optimal empirical Performance of teams with respect to all the IPL teams India. The team wise Performances is evaluated by considering the Efficiency of one team over rest of the teams under various permutations of inputs and outputs by computing the Technical Efficiency (T.E), Pure Technical Efficiency(P.T.E), Scale Efficiency, constant returns to scale (CRS), variable returns to scale (VRS), along with Reference set , Peers and rank of the decision-making units. Based on the reference set and peerweight in this analysis,we can express the input and output values needed to bring every DMUs into an efficient frontier. Also, by CCR and BCR theoretical models we evaluate the Technical Efficiency (TE) and Pure Technical Efficiency (PTE) of the teams for the data are presented.